The influence of stimulus repetition on duration judgments with simple stimuli - Birngruber, Teresa; Schröter, Hannes; Ulrich, Rolf (Frontiers in Psychology, 2015)
Two experiments investigated the effects of stimulus repetition versus stimulus novelty on perceived duration. In a reminder task, a standard and a comparison stimulus were presented consecutively in each trial, and the comparison was either a repetition of the standard or a different stimulus. Pseudowords (Experiment~1) or strings of consonants (Experiment~2) were used as stimuli and the inter-stimulus interval between the standard and the comparison was either constant or variable. Participants were asked to judge whether the comparison was shorter or longer than the standard. In both experiments, we observed shorter judged durations for repeated than for novel comparisons whereas the manipulation of the inter-stimulus interval had no pronounced effects on duration judgments. The finding of shorter duration judgments for repeated as compared to novel nonwords replicates the results of a previous study (Matthews, 2011) which employed highly complex stimulus material. The present study shows that changes of simple, semantically meaningless stimuli are sufficient to result in a shorter perceived duration of repeated as compared to novel stimuli.